PENERAPAN BIAYA KUALITAS UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA PT. PERTANI (PERSERO) CABANG SULAWESI UTARA - Bawon, Dwi Nugraha Pratiwi; Sondakh, Jullie J.; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Quality is one of the main factors that must be considered by the company to be able to survive in the competition. By Continuous quality improvement, it will reduce the cost of quality that occurs due to low quality product, rework a product for conformance to standards and others. Decrease in quality costs will increase profits and reduce costs, especially the cost of production. This is because the cost of quality is part of the cost of production. The purpose of this study was to determine whether the company has implemented and report quality costs andÂ  to find out if Is the application of quality costs can increase the cost efficiency of production at PT Pertani branch north sulawesi. Data analysis tool used is descriptive analysis method of analysis with a quantitative approach. Research shows that in 2011 the cost of quality production unit PT Pertani branch north Sulawesi amounting to Rp 365,390,718. By doing repairs, the cost of quality will be decreased by Rp 127,657,118. Therefore, if companies implement and report quality costs companies can improve efficiency of production costs.